Proteinuria in Two Sisters with Beaulieu-Boycott-Innes Syndrome, A Case Report (Iranian Journal of Kidney Diseases, 2020)
We report two sisters (13- and 4-year-old) presenting with moderate intellectual disability, dysmorphic facial features, intermittent hematuria, proteinuria, and dental caries. Their parents and other family members were not affected. Whole-exome sequencing was performed to screen the underlying genetic cause. These patients have been analyzed using Next-Generation Sequencing (NGS) method and homozygote variant (c.890delC) has been detected in the THOC6 gene. Direct Sanger sequencing confirmed that they are homozygote for the pathogenic variant mutations in the THOC6 gene, which is associated with Beaulieu-Boycott-Innes syndrome (BBIS). These patients also had proteinuria and subsequently developed hematuria. This is the first report of BBIS in association with proteinuria and hematuria without renal defects. Core clinical features include low birth weight with subsequent growth failure, short stature, and intellectual disability with language delay, characteristic faces, cardiac defects, and renal anomalies. The possible pathophysiological mechanisms associated with proteinuria and transient hematuria without renal defects are discussed.